The Effect Of Hotel Tax Collection, Restaurant Tax And Entertainment Tax On The Original Regional Density In Medan City - Muhammad Fahmi Hilfandi; Rico Nur Ilham; Marzuki Marzuki; Jummaini Jummaini; Rusydi Rusydi (Journal of Accounting Research, Utility Finance and Digital Assets, 2022)
This study aims to examine the effect of hotel tax collection, restaurant tax and entertainment tax on the original regional density in Medan City. This study used time series data for 2016-2020 obtained from the Medan City Regional Tax and Levy Management Agency. The data analysis method used is the multiple linear regression method with the help of SPSS 25. The results of the study partially showed that the Hotel Tax had a positive and significant effect on Regional Original Income in Medan City, Restaurant Tax had a positive and significant effect on Regional Original Income in Medan City, and Entertainment Tax showed results of negative and insignificant effects on Regional Original Income in Medan City. Simultaneously, the simultaneous results of the variables hotel tax, restaurant tax, and entertainment tax have a positive and significant effect on the original regional income in Medan city.